Asymmetric Adjustment and Nonlinear Dynamics in Real Exchange Rates - Leon, Gene (IMF Working Papers; Working Paper, 2003)
This paper examines whether deviations from PPP are stationary in the presence of nonlinearity, and whether the adjustment toward PPP is symmetric from above and below. Using alternative nonlinear models, our results support mean reversion and asymmetric adjustment dynamics. We find differences in magnitudes, frequencies, and durations of the deviations of exchange rates from fixed and time-varying thresholds, both between over-appreciations and over-depreciations and between developed and developing countries. In particular, the average cumulative sum of deviations during periods when exchange rates are below forecasts is twice that of the sum during periods of over-appreciation, and is larger for developing than for advanced countries.